(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Sushentseva L. Theoretical justification model for the formation of professional Mobile Future skilled worker. In article the author is proved model of professionally mobile qualified worker and model of process of formation of professional mobility of the future qualified worker.